Unsteady Pressure Measurement Of NACA 0018 Undergoing Pure Pitching Motion At Different Pitch Amplitudes - Tong, Chee Kent (Universiti Sains Malaysia, 2017)
An experimental investigation of the unsteady pressure measurement of a 2D NACA 0018 airfoil oscillating in pitch motion was performed by using pressure transducers at open-circuit wind tunnel. In the case of study, the wind tunnel testing was conducted in low flight regimes (